Power Oscillations Damping in DC Microgrids - Hamzeh, Mohsen; Ghafouri, Mohsen; Karimi, Houshang; Sheshyekani, Keyhan; Guerrero, Josep M. (IEEE transactions on energy conversion, 2016)
This paper proposes a new control strategy for damping of power oscillations in a multisource dc microgrid. A parallel combination of a fuel cell (FC), a photovoltaic system, and a supercapacitor (SC) is used as a hybrid power conversion system (HPCS). The SC compensates for the slow transient response of the FC stack. The HPCS controller comprises a multiloop voltage controller and a virtual impedance loop for power management. The virtual impedance loop uses a dynamic droop gain to actively damp the low-frequency oscillations of the power sharing control unit. The gain of the virtual impedance loop is determined using a small-signal analysis and the pole placement method. The Mesh analysis is employed to further study the stability of low-frequency modes of the overall dc microgrid. Moreover, based on the guardian map theorem, a robust stability analysis is carried out to determine a robustness margin for the closed-loop system. The main advantage of the proposed method is its robustness against uncertainties imposed by microgrid parameters. This feature provides DG units with plug-and-play capability without needing the exact values of microgrid parameters. The performance of the proposed control scheme is verified using hardware-in-the-loop simulations carried out in OPAL-RT technologies.